Bone marrow infiltration pattern in patients with intravascular large B‐cell lymphoma diagnosed by random skin biopsy. Issue 1 (20th July 2020) - Matsue, Kosei; Abe, Yoshiaki; Narita, Kentaro; Kobayashi, Hiroki; Kitadate, Akihiro; Miura, Daisuke; Takeuchi, Masami; Takeuchi, Kengo
Abstract: We retrospectively analyzed bone marrow (BM) infiltration pattern in consecutive 30 intravascular large B‐cell lymphoma (IVLBCL) patients diagnosed by random skin biopsy (RSB). BM infiltration of lymphoma was observed in 18 patients (60.0%), including five patients with the intrasinusoidal pattern with minimal extravasation, eight patients with the mixed of intrasinusoidal and scattered/interstitial or nodular infiltration, and five patients with the nodular/diffuse pattern. Twelve patients were negative for lymphoma infiltration. BM histology of patients with IVLBCL were diverse and frequently discordant with those of other site of IVLBCL lesions. BM biopsy had a poorer diagnostic performance for detecting intravascular features.